2013
DOI: 10.1212/wnl.0b013e3182a9f3b4
|View full text |Cite
|
Sign up to set email alerts
|

Quinacrine treatment trial for sporadic Creutzfeldt-Jakob disease

Abstract: This study provides Class I evidence that quinacrine does not improve survival for people with sCJD when given orally at a dose of 300 mg per day for 2 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
87
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(93 citation statements)
references
References 34 publications
3
87
0
3
Order By: Relevance
“…Tragically, in no case did treatment provide discernible benefits (10)(11)(12)(13)(14)(15). Possibly related to this failure, studies in mice lacking the multiple drug resistant gene inoculated with RML prions and orally dosed with quinacrine resulted in selection and propagation of quinacrineresistant prions (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tragically, in no case did treatment provide discernible benefits (10)(11)(12)(13)(14)(15). Possibly related to this failure, studies in mice lacking the multiple drug resistant gene inoculated with RML prions and orally dosed with quinacrine resulted in selection and propagation of quinacrineresistant prions (28).…”
Section: Discussionmentioning
confidence: 99%
“…Based on initial reports of quinacrine's effects on mouse prion propagation in cell culture, a plethora of studies were designed to discern the mechanism of its presumed antiprion effects (19,20,(29)(30)(31)(38)(39)(40)(41)(42)(43)(44)(45), to assess its pharmacokinetics (21,36,42,46) and to derive similar compounds with improved antiprion efficacy (18,20,(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). These studies continue to this day, despite multiple failed clinical studies in patients with human prion diseases (10)(11)(12)(13)(14)(15). The findings reported here force a reconsideration of current strategies to screen antiprion drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Along with a stream of evidence-based medicine, several clinical trials have recently been performed within a structured framework, including flupirtine trials in Germany (Otto et al 2004), quinacrine trials in the United Kingdom (Collinge et al 2009) and United States (Geschwind et al 2013), and doxycycline trials in Italy and France . Table 1 summarizes these clinical trials and their results, and each trial is described in detail in the following section.…”
Section: Historical Overview Of Medical Interventions For Cjdmentioning
confidence: 99%
“…This study concluded that there was no difference in mortality between the treated and untreated groups. Another clinical trial of quinacrine conducted in the United States from 2005 to 2009 in a double-blind, placebo-controlled, stratified-randomization manner concluded that quinacrine did not increase survival of sporadic CJD patients compared with the placebo (Geschwind et al 2013). …”
Section: Flupirtinementioning
confidence: 99%
“…In our sporadic Creutzfeldt-Jakob disease trial of quinacrine, 2 we off ered open-label treatment to patients returning for their 2 month study visit because we were concerned that patients would not enrol if they were not eventually off ered active treatment. This turned out to be a weakness of our trial design, because the 2 month randomised phase might have been too short.…”
Section: -3mentioning
confidence: 99%